2018
DOI: 10.1016/j.cct.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Applying Interactive Mobile health to Asthma Care in Teens (AIM2ACT): Development and design of a randomized controlled trial

Abstract: Early adolescents have difficulties performing asthma self-management behaviors, placing them at-risk for poor asthma control and reduced quality of life. This paper describes the development and plans for testing an interactive mobile health (mHealth) tool for early adolescents, ages 12-15years, and their caregivers to help improve asthma management. Applying Interactive Mobile health to Asthma Care in Teens (AIM2ACT) is informed by the Pediatric Self-management model, which posits that helpful caregiver supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 47 publications
(59 reference statements)
0
40
0
Order By: Relevance
“…A further eight studies were excluded, use of mobile phones was restricted to sending text messages/phone calls in two papers [ 15 , 16 ], results were combined for children and adults in three [ 17 , 18 , 19 ], and three were trial protocols [ 20 , 21 , 22 ]. After applying the exclusion criteria, eight studies remained on the use of phone technology in asthma self-management among asthmatic children and adolescents ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A further eight studies were excluded, use of mobile phones was restricted to sending text messages/phone calls in two papers [ 15 , 16 ], results were combined for children and adults in three [ 17 , 18 , 19 ], and three were trial protocols [ 20 , 21 , 22 ]. After applying the exclusion criteria, eight studies remained on the use of phone technology in asthma self-management among asthmatic children and adolescents ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Involvement of stakeholders in the development of technology-based interventions is an important part of UCD to ensure systems match users’ needs [25]. Using interviews to learn about stakeholders needs have been used among a variety of different groups including people with mental illness [37], among parents and teenagers with asthma [38], and for improving physical activity among people with chronic illnesses [39]. These studies found similar results, suggesting that intervention content should be highly relevant to stakeholders' needs, and in an easy-to-use format [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…This study looked at the association between adherence with asthma medications and the patient-provider relationship in early adolescents. Data came from baseline data collected through an ongoing longitudinal study titled AIM2ACT: Applying Interactive Mobile health to Asthma Care in Teens (Fedele et al 2018). Pharmacy refill data was obtained by phoning the participants' pharmacies and recording the number of times their inhaled corticosteroids (ICS) were filled over the 12-month period prior to enrollment in the study.…”
Section: Methodsmentioning
confidence: 99%